Molecular characterization of the pathogen-specific, 34-kilodalton membrane immunogen of Treponema pallidum. - Swancutt, M A (1989)
The 34-kilodalton (kDa) antigen of Treponema pallidum subsp. pallidum (T. pallidum) is a pathogen-specific integral membrane protein. DNA sequence analysis of the cloned gene revealed an open reading frame encoding a primary product of 204 residues with a molecular mass of 22,087 daltons. Sequences that correspond to a consensus Escherichia coli promoter and a ribosome-binding site were found upstream from the AUG start codon that begins the open reading frame, suggesting that the cloned gene can use its own regulatory sequences for expression. Examination of the deduced amino acid sequence revealed the presence of a typical procaryotic leader peptide 19 amino acids long; processing results in a mature molecule with a molecular mass of 20,123 daltons. Pulse-chase experiments with E. coli minicells confirmed that the 34-kDa antigen is synthesized as a higher-molecular-weight precursor that is processed to a mature form with the electrophoretic mobility that is characteristic for this protein. The presence in the leader peptide of the sequence Phe-Ser-Ala-Cys suggested that the 34-kDa antigen is a proteolipid. Although hydropathy analysis of the deduced amino acid sequence of the mature 34-kDa antigen predicted that the molecule was primarily hydrophilic, both the native and recombinant 34-kDa molecules displayed hydrophobic biochemical behavior by fractionating into the detergent phase after extraction of intact organisms with Triton X-114. Cell fractionation experiments with E. coli showed that the 34-kDa molecule was localized in both the inner and outer membranes of the recombinant host. The combined data demonstrate that the 34-kDa antigen is an integral membrane protein that behaves in a biochemically consistent manner in both T. pallidum and E. coli.